Molecular basis of Mycoplasma surface antigenic variation: a novel set of divergent genes undergo spontaneous mutation of periodic coding regions and 5′ regulatory sequences - Yogev, D.; Rosengarten, R.; Watson‐McKown, R.; Wise, K.S. (The EMBO journal, 1991)
Antigenic diversity is generated in the wall‐less pathogen Mycoplasma hyorhinis by combinatorial expression and phase variation of multiple, size‐variant membrane surface lipoproteins (Vlps). The unusual structural basis for Vlp variation was revealed in a cluster of related but divergent vlp genes, vlpA, vlpB and vlpC, which occur as single chromosomal copies. These encode conserved N‐terminal domains for membrane insertion and lipoprotein processing, but divergent external domains undergoing size variation by loss or gain of repetitive intragenic coding sequences while retaining a motif with distinctive charge distribution. Genetic analysis of phenotypically switched isogenic lineages representing ON or OFF expression states of Vlp products ruled out chromosomal rearrangement or frameshift mutations as mechanisms for Vlp phase variation. However, highly conserved vlp promoter regions contain a tract of contiguous A residues immediately upstream of the −10 box which is subject to frequent mutations altering its length in exact correspondence with the ON and OFF phase states of specific genes. This suggests a mechanism of transcriptional control regulating high frequency phase variation and random combinatorial expression of Vlps. The multiple levels of diversity embodied in the vlp gene cluster represents a novel adaptive capability particularly suited for this class of wall‐less microbe.